2020
DOI: 10.1177/1359105320937059
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of transcranial direct current stimulation in children and adolescents with ADHD: The point of view of parents

Abstract: Transcranial direct current stimulation (tDCS) is a novel treatment option for attention deficit hyperactivity disorder. To facilitate translation into clinical practice, we interviewed parents of children who have experienced experimental tDCS. A grounded theory approach using open, axial, and selective coding provided seven emergent themes for acceptability: tDCS provides hope for parents, safety tolerability and side effects of tDCS versus medication, burden of treatment, education and trust with care provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Under this definition "rate of dropouts = acceptability", tDCS appears to be very acceptable in children and adolescents. That being said, recent research [8,47] has demonstrated that defining acceptability by rate of dropouts can be limited. Specifically, parents of children who have underwent tDCS were interviewed regarding tDCS acceptability: for them, tDCS acceptability was primarily dependent on efficacy, availability, cost, and side effects compared to medication [8].…”
Section: Acceptability and Rate Of Dropoutsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this definition "rate of dropouts = acceptability", tDCS appears to be very acceptable in children and adolescents. That being said, recent research [8,47] has demonstrated that defining acceptability by rate of dropouts can be limited. Specifically, parents of children who have underwent tDCS were interviewed regarding tDCS acceptability: for them, tDCS acceptability was primarily dependent on efficacy, availability, cost, and side effects compared to medication [8].…”
Section: Acceptability and Rate Of Dropoutsmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) is a non-invasive neuromodulation technique considered to be safe, tolerable, and acceptable to use in adults [1][2][3][4][5][6][7][8]. However, it is minimally researched and still controversial in pediatrics [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to provide these patients with alternative treatment options that may be more suitable to their needs. In a study comparing the acceptability of tDCS to pharmaceuticals, subjects were consistently partial to tDCS [20]. Interestingly, this is also the case in children [20].…”
mentioning
confidence: 93%
“…In a study comparing the acceptability of tDCS to pharmaceuticals, subjects were consistently partial to tDCS [20]. Interestingly, this is also the case in children [20]. Therefore, the community is prepared to embrace the uptake of tDCS if its efficacy is established.…”
mentioning
confidence: 99%
See 1 more Smart Citation